B- thalassemia children and quality of life: Does the present condition justify ‎children's quality of life?‎ - simin tahmasbi; fereshteh aein; fereshteh heravi karimuoe (Guilan University of Medical Sciences, 2007)
Introduction:‎‏ ‏Annually,‎‏ ‏thousands of children are born with B- thalassemia major who ‎receive continuous treatment.‎‏ ‏The goals of treatments are providing these children quality of ‎life (QOL).‎ Objective: The purpose of this study is to determine the QOL of children with B-thalassemia ‎referring to thalassemia centers from their point of view and assessing its effective factors.‎ Methods‏ :‏‎ In this descriptive – analytic study, the Red QOL scale and a questionnaire in ‎‏3‏‎ ‎domains of demographic, social and treatment factors were used to interview with ‎‏34‏‎ ‎Children with B-thalassemia major referring to selected thalassemia wards. Data were ‎analyzed by descriptive and analytic statistics and SPSS software.‎ Results:‎‏ ‏The mean score of children s Qol in physical domain was ‎‏11 ‏‎±‎‏ 5‏‎.‎‏59‏‎, social domain ‎‏4‏‎.‎‏85 ‏‎±‎‏ 3‏‎.‎‏56‏‎ , school practice ‎‏7‏‎.‎‏14‏‎ ± ‎‏3‏‎.‎‏72‏‎ and cummulatively QOL domains was equal to ‎‏30.29‏‎ ‎‎±‎‏ 13.38‏‎. Also such factors such as availability of blood, medicine, personnel s relation, school ‎health nurse, number of hospitalization due to related problems had significant relationship ‎with some of the children s QOL domains. ‎ Conclusion: Based on study findings, the QOL condition of children with thalassemia was ‎satisfactory. It appears that the medical services provided to these children in centers are ‎satisfactory and maintains the objectives.‎